THE METHODOLOGICAL DESCRIPTION OF IMPROVING THE SPEECH COMPETENCE OF FUTURE FOREIGN LANGUAGE TEACHERS - Gaffarova, Dilafruz Vaydulla qizi (Educational Research in Universal Sciences, 2023)
This article provides a methodological description of how to improve the speech competence of future foreign language teachers. Effective communication skills are crucial for language instructors, and speech competence plays a vital role in facilitating comprehension, modeling correct pronunciation, and creating an engaging learning environment. The article emphasizes the importance of pronunciation, intonation, fluency, and communicative skills in language teaching. It explores various methodologies for enhancing speech competence, including language immersion, pronunciation practice, technology integration, and cultural competence development. The article also highlights the significance of continuous professional development, peer collaboration, and assessment and feedback in the improvement process. By following these methodological approaches, future foreign language teachers can enhance their speech competence, leading to more effective language instruction and enhanced learning outcomes for their students.